Nutritional Composition of Five Varieties of Pap Commonly Consumed in Maroua (Far-North, Cameroon) - Ponka Roger; Bouba Armand Abdou; Fokou Elie; Beaucher Eric; Piot Michel; Leonil Joëlle; Gaucheron Frédéric (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to determine the nutritional composition of five varieties of pap (cereal product) commonly consumed in Maroua, city of the Far-North Region of Cameroon. The proximate composition (moisture, ash, protein, lipid, and crude fibre) was determined by standard AOAC methods. Minerals (calcium, magnesium, sodium, potassium, iron, zinc, copper and manganese) were determined by atomic absorption spectrophotometry and phosphorus was determined colorimetrically. Amino acid composition was determined by ion-exchange chromatography. All the pap varieties had a very high carbohydrate content (79.47-85.29 g/100 g dry matter). Appreciable levels of phosphorus and potassium were recorded in all the pap varieties (137.5-231.0 mg/100 g dry matter and 198.20-322.22 mg/100 g dry matter, respectively). Consumption of each pap (100 g) by children 1-2 year old would meet 9.86-17.46% and 0.08-19.51% of their daily recommended intake respectively for protein and minerals. Leucine and glutamic acid were the most abundant essential amino acids and non-essential amino acids respectively in the pap. Essential amino acids in most of the pap samples met the recommended children requirement of the FAO/WHO/UNU for 1-2 year old children except methionine+cysteine and lysine.